Condensation of Amines with S-Methyl Thiouronium Salts: Another Entry for the Synthesis of Amidines - Swaroop, Toreshettahally R.; Bakyyev, Rahym; Rangappa, Kanchugarakoppal S.; Torun, Lokman (Synlett, 2024)
We present a condensation of primary aryl or alkyl amines with S-methyl thiouronium salts to obtain N,N,N′-trisubstituted amidines. High yields, short reaction times, and a fair substrate scope are the noteworthy features of this protocol. Surprisingly, the reaction of a thiouronium salt with 4-aminopyridine gave 1-(4-methoxybenzoyl)piperidine.
Keywords: amidines; condensation; thiouronium salts; amides; amines